Effective Use of Financial Funds of Commercial Banks in the Development of Real Sector Enterprises - Umedov, Dilshod (European Journal of Life Safety and Stability (2660-9630), 2022)
In the development of real sector enterprises, the banking system in recent years has been working to improve the quality and scope of modern banking services. This article develops recommendations for the effective use of financial resources of commercial banks in the development of real sector enterprises.